A brew to a kill - Coyle, Cleo (New York : Berkley Prime Crime, 2013)
"A shocking hit-and-run in front of her Village Blend coffeehouse spurs Clare Cosi into action. A divorced, single mom in her forties, Clare is also a dedicated sleuth, and she's determined to track down this ruthless driver who ran down an innocent friend and customer. In the meantime, her ex-husband Matt, the shop's globetrotting coffee buyer, sources some amazing new beans from Brazil. But he soon discovers that he's importing more than coffee, and Clare may have been the real target of that deadly driver. Can ex-husband and wife work together to solve this mystery-or will their newest brew lead to murder?" -- Publisher's website.
Reprint. Originally published: 2012.
"Includes coffee cake & muffin recipes!"--Cover.
Keywords: Cosi, Clare (Fictitious character) -- Fiction; Coffeehouses -- Fiction; Murder -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction